Intrusion Detection System (Ids) Menggunakan Raspberry Pi 4 dengan Snort Studi Kasus : Laboratorium Jaringan Komputer Politeknik Negeri Bengkalis - wahyat, Wahyat; Ryci Rahmatil Fiska; Dedi Hermawan (Politeknik Negeri Bengkalis, 2023)
Server security on a computer network is very important, maintaining computer network security in order to maintain information, data and maintain infrastructure so that it can work and function properly and provide access rights to registered users, this study aims to build an Intrusion Detection System (IDS) on networks and servers using Raspberry Pi 4 with SNORT which is useful for monitoring Server activities when an attempted attack occurs by sending notifications to BOT Telegram via the administrator's cellphone in realtime, this system is tested with three attack scenarios namely, PING Attack, Port Scanning, and DOS / DDoS Attack. From the results of testing attacks, Snort can detect and provide alerts that will be stored in the Snort Log and forwarded to the Telegram BOT notification in real time. Keywords: Raspberry pi, Server, IDS, Snort, Bot Telegram